Pengaruh Perbandingan Pupuk dan Macam Media Tanam Hidroponik Sistem Wick Terhadap Pertumbuhan dan Hasil Sawi Dakota (Brassica rapa L): AB Mix, Brassica rapa L, Hidroponik Sumbu, Media Tanam, POC - Hartanti, Sri; Hadi, Pramono; Rachmawatie, Srie Juli (Folium : Jurnal Ilmu Pertanian, 2025)
Wick hydroponics (Wick) is the simplest method, because it does not use electricity. The purpose of the study was to determine the best fertilizer ratio and type of planting media for Dakota mustard plants. The study used a Randomized Complete Block Design Split Plot, which consisted of 2 factors, namely Fertilizer Ratio (P) with treatment: P0: 100% AB Mix, P1: POC Ratio 70% : 30% AB Mix, P2: Ratio 50% : 50% AB Mix, and Planting Media (M) namely M0: Rockwool, M1: Cotton, M2: Rice Husk Charcoal. The results showed that the P treatment had a very significant effect on all parameters. The M treatment had a significant effect on plant height, fresh weight of plants, and plant consumption weight, and had a very significant effect on leaf width and root length. The combination of fertilizer ratio treatment and type of planting media in P0M2 (100% AB Mix and rice husk charcoal planting media) had a very significant effect on leaf width, fresh weight, and consumption weight of Dakota mustard plants.